2017
DOI: 10.4269/ajtmh.16-0435
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pentoxifylline Associated with Pentavalent Antimony: A Randomized Trial for Cutaneous Leishmaniasis

Abstract: Cutaneous leishmaniasis (CL) by is associated with decreasing cure rates in Brazil. Standard treatment with pentavalent antimony (Sb) cures only 50-60% of the cases. The immunopathogenesis of CL ulcer is associated with high interferon-γ and tumor necrosis factor (TNF) production. Pentoxifylline, a TNF inhibitor, has been successfully used in association with Sb in mucosal and cutaneous leishmaniasis. This randomized, double-blind, and placebo-controlled trial aimed to evaluate the efficacy and safety of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
4
21
1
1
Order By: Relevance
“…Those studies have shown that the combination of Sb v with PTX led to the healing of lesions of refractory cases of ML, as well as a higher cure rate when compared with Sb v and placebo in a controlled randomized trial. 12,15,16,19 This was also observed here. Although the time of healing varied in the To better understand the mechanisms that led to this successful treatment, we evaluated the cellular composition of lesions from patients treated with Sb v alone and with the combination of PTX with Sb v , as well as cytokine and granzyme A expression, which are involved in immunoregulation and cytotoxic activity, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Those studies have shown that the combination of Sb v with PTX led to the healing of lesions of refractory cases of ML, as well as a higher cure rate when compared with Sb v and placebo in a controlled randomized trial. 12,15,16,19 This was also observed here. Although the time of healing varied in the To better understand the mechanisms that led to this successful treatment, we evaluated the cellular composition of lesions from patients treated with Sb v alone and with the combination of PTX with Sb v , as well as cytokine and granzyme A expression, which are involved in immunoregulation and cytotoxic activity, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The meglumine antimoniate associated with pentoxifylline (Machado et al 2007) were classified as clinically useful and with acceptable risk with specialized monitoring (Machado et al 2007 [15]). On the other hand the combination of meglumine antimoniate associated with pentoxifylline performed by Brito et al 2017 [31] to treat cutaneous leishmaniasis caused by Leishmania braziliensis was classified as not efficacious and not useful. Meglumine antimoniate associated with omeprazole (Nilforoushzadeh et al 2008 [26]) was classified as clinically useful and with acceptable risk with specialized monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…4,15 Other studies also indicate that in CL patients with severe lesions caused by Leishmania braziliensis, anti-TNF treatment can help the healing process and enhance ulcer cicatrization, 16 although no consensus has been established. 17 In the present case, it is difficult to determine whether the severity of the CL symptoms was due to the concomitant disease, the administration of anti-TNF drugs or cortisone, or a combination of factors.…”
Section: Discussionmentioning
confidence: 72%